Potentially preventable hospitalizations—The 'pre‐hospital syndrome': Retrospective observations from the MonashWatch self‐reported health journey study in Victoria, Australia. Issue 2 (28th August 2020) - Martin, Carmel; Hinkley, Narelle; Stockman, Keith; Campbell, Donald
Abstract: Rationale, Aims, and Objectives: HealthLinks: Chronic Care is a state‐wide public hospital initiative designed to improve care for cohorts at‐risk of potentially preventable hospitalizations at no extra cost. MonashWatch ( MW) is an hospital outreach service designed to optimize admissions in an at‐risk cohort. Telehealth operators make regular phone calls (≥weekly) using the Patient Journey Record System (PaJR). PaJR generates flags based on patient self‐report, alerting to a risk of admission or emergency department attendance. 'Total flags' of global health represent concerns about self‐reported general health, medication, and wellness. 'Red flags' represent significant disease/symptoms concerns, likely to lead to hospitalization. Methods: A time series analysis of PaJR phone calls to MW patients with ≥1 acute non‐surgical admissions in a 20‐day time window (10 days pre‐admission and 10 days post‐discharge) between 23 December 2016 and 11 October 2017. Pettitt's hypothesis‐testing homogeneity measure was deployed to analyse Victorian Admitted Episode/Emergency Minimum Datasets and PaJR data. Findings: A MW cohort of 103 patients (mean age 74 ± 15 years; with 59% males) had 263 admissions was identified. Bed days ranged from <1 to 37.3 (mean 5.8 ± 5.8; median 4.1). The MW cohort had 7.6 calls on average in the 20‐day pre‐ and post‐hospital period. Most patients reported significantly increased flags 'pre‐hospital' admission: medication issues increased on day 7.0 to 8.5; total flags day 3, worse general health days 2.5 to 1.8; and red flags of disease symptoms increased on day 1. These flags persisted following discharge. Discussion/Conclusion: This study identified a 'pre‐hospital syndrome' similar to a post‐hospital phase aka the well‐documented 'post‐hospital syndrome'. There is evidence of a 10‐day 'pre‐hospital' window for interventions to possibly prevent or shorten an acute admission in this MW cohort. Further validation in a larger diverse sample is needed.